Competing frames over the Grand Ethiopian Renaissance Dam in the Egyptian and Ethiopian media - Aynalem, Desalegn; Zerai, Abdissa (Frontiers in Communication, 2025)
The Grand Ethiopian Renaissance Dam, a 6,000-megawatt project on the Blue Nile, is an epicenter of exacerbated disputes and confrontations between riparian states, garnering the attention of both local and international media. This article examines the salient frames of Ahram Online and the Ethiopian Herald, state run national newspapers in Egypt and Ethiopia, respectively. Guided by Framing Theory, the study employed an inductive qualitative frame analysis method. A total of 289 news stories, collected from the online archives of the newspapers, spanning from January 2017 to December 2022, were analyzed. Findings reveal that six dominant frames and six counter-frames emerge from Ahram Online and the Ethiopian Herald, respectively. The frames and counter-frames emerged are, ‘Historic right’ Vs. ‘Tributary right,’ ‘National threat’ Vs. ‘National pride,’ ‘Power domination’ Vs. ‘Regional integration,’ ‘Necessity of binding agreement’ Vs. ‘Obsession with colonial treaties,’ ‘Unyieldingness’ (for both) and ‘Unilateral act’ Vs. ‘Right to development’ frames. This study argues that such polarized and bifurcated depiction of the dam on the media has contributed to conflicting rather than cooperative relationship between the two riparian countries.